Fundamental principles of the concept of health-forming technologies in the process of physical education of primary-school aged children - Nataliia Goncharova (Kazimierz Wielki University, 2017)
On the basis of the data from scientific and methodological resources up-to-date development trends in the process of physical education in the general secondary education establishments are defined in the publication. Best scientific practices in the field of health-forming activity are considered. The aim of the research is to distinguish theoretical basis of the concept of health-forming technologies in the process of physical education of primary-school aged children. The following research methods were used in order to achieve the aim of the investigation: analysis and generalization of the data from scientific and methodological resources, Internet sources, content analysis, concept and term analysis, theoretical and methodological analysis. Justification of the concept of health-forming technologies in the process of physical education of primary-school aged children, which meets key provisions of the concept structure, is offered. The aim, objectives, main principles of the concept functioning, including didactic principles, the principles of physical education and specific principles of health-forming activity (innovative design, health-forming validity, dominant of child's health, three-pronged concept of health, teacher's competence, systemacity) are defined. Conceptual approaches, necessary for presenting the scope of generalized scientific ideas from the field of children's health formation, organization of theoretical and practical activity in regards to research. Conceptual approaches of general scientific methodological level (systematic, synergetic, activity, dialectical) as well as the approaches of specific scientific methodological level (person-centered, differentiated, axiological, participative, sociocultural) are characterized. The main activity areas within the frames of the concept implementation, health-forming technology as a part of the introduced concept are systematized.